Bioactive diamond scaffolds support neuronal survival and axonal growth - R J F Sørensen; Nicolas Bertram; Ugne Dubonyte; Bob A Hersbach; Alison Salvador; Anpan Han; Agnete Kirkeby; Rune W Berg; Jaspreet Kaur (Engineered Regeneration)
Injury to the central nervous system (CNS) can have devastating consequences for the individual, and strategies to promote endogenous axonal regeneration may be a promising future therapeutic avenue. In the case of spinal cord injury, one approach is to generate a scaffold-bridge across the injury site, through which the neuronal axons can grow and reconnect. Inspired by the various properties of diamond, including its chemical inertness, we proposed a strategy in which synthetic diamond scaffolds were coated with proteins with beneficial properties to promote biocompatibility of the scaffolds towards neurons. Here, we demonstrated that bare, non-coated diamond scaffolds, when terminated with either oxygen or hydrogen, were unable to adhere to the human embryonic stem cell-derived interneurons in culture. In contrast, oxygen terminated protein-coated scaffolds (i.e., bioactive diamond scaffold) efficiently enabled neuronal attachment and supported the survival, migration, and neurite elongation across an induced injury gap in culture. Further, hydrogen terminated bioactive scaffolds also promoted cell adhesion, migration, and neurite elongation upon injury, but not as efficiently as oxygen-terminated bioactive scaffolds. With this data we suggest that bioactive synthetic diamond scaffolds could provide a valuable tool for future therapeutic strategies in the context of CNS injuries.